Intimacy in America : dreams of affiliation in antebellum literature - Coviello, Peter (University of Minnesota Press, 2005)
Reading seminal works by Thomas Jefferson, Edgar Allan Poe, Herman Melville, Harriet Beecher Stowe, and Walt Whitman, Peter Coviello traces these writers' ambivalences about the idea of an intimate nationality, revealing how race and sexuality were used as vehicles for an assumed coherence. Intimacy in America gives us a new perspective on the dream of Americanness as a relation to anonymous others.